Design innovation and user experience of sensory interactive experience in museum exhibition space - Ji, Yijing; Lin, Qianqian; Yin, Wenjuan; Han, Bing; Jiang, Yirui (IOS Press, 2024)
This research examines the influence of multi-sensory experiences on visitor engagement within museums in the United Kingdom, with particular emphasis on the roles of physical design elements, technological integration, and sensory stimuli. Utilizing a comprehensive literature review, along with observational studies and surveys across 12 specialized museums, this study identifies critical factors that enhance visitor interaction and satisfaction. The findings reveal that the incorporation of interactive and multi-sensory elements, such as augmented reality and tactile exhibits, significantly augments visitor engagement. This study highlights the evolving function of museums as dynamic educational platforms that amalgamate entertainment and learning. It underscores the imperative for future museum designs to adapt to the digital era and cater to the diverse expectations of visitors. The results suggest that a strategic integration of sensory experiences can transform museums into more inclusive and immersive environments, thereby enriching the educational and cultural experiences of their audiences.
Keywords: 4302 Heritage, Archive and Museum Studies; 43 History, Heritage and Archaeology